An Analysis Of Working System Carcinogenic Substance Neutralization Tool (Smoke/Gas) In A Closed Space Using An Arduino Uno-Based MQ3 Sensor - Nuraprilyani Pasaribu; Beni Satria; Ahmad Dani (Sean Institute, 2025)
This study aims to analysed the working system of a carcinogenic substance neutralization device for smoke or gas in enclosed spaces, using an MQ3 sensor based on Arduino Uno. Carcinogenic substances in the form of smoke or gas can pose significant health risks, especially in areas with limited air circulation. The device developed in this research utilizes the MQ3 sensor to detect harmful gases, which are then processed through Arduino Uno to automatically activate the neutralization system. The research method involves the design, assembly, and testing of the neutralization system. The MQ3 sensor functions as a detector for hazardous gases at specific concentration levels, sending data to the Arduino Uno, which triggers the activation of a fan and air filter as the neutralization system. Testing was conducted in an enclosed space to evaluate the effectiveness of the system in reducing harmful gas concentrations over a given period. The results indicate that this neutralization device effectively detects and significantly reduces harmful gas concentrations. The MQ3 sensor is highly responsive to changes in gas levels, and the Arduino Uno-based system allows for efficient automated control. With these results, the device is expected to serve as a solution for improving indoor air quality and protecting users from exposure to carcinogenic substances.